PENEMUAN HUKUM DALAM TAFSIRAN INKONSTITUSIONAL BERSYARAT PADA PUTUSAN MAHKAMAH KONSTITUSI(Analisis Putusan Mahkamah Konstitusi Nomor : 46/PUU-VIII/2010) - Nana Supena (2022)
This study was conducted to examine the finding of conditional inconstitutional interpretation law in the decision of the Constitutional Court, which focused on the Constitutional Court Decision Number: 46/PUU-VIII/2010. This study is motivated by the broad authority of the Constitutional Court in interpreting the constitution, including various decisions that are considered controversial. The results of the study show that the 1945 Constitution implicitly gives the Constitutional Court the authority to interpret the constitution to assess the conflicting legal norms in examining the constitutionality of the law. Some of the interesting things in implementing the interpretation of the constitution as a benchmark for assessing conflicting legal norms, include: First, related to the independence and freedom of judges in using interpretive methods that are not regulated in positive law, judges are free to use the interpretation method that is in accordance with the judge's belief. Second, the emergence of conditional inconstitutionality in the Constitutional Court's decision is considered a form of abuse of power in interpreting the law, even though in fact the interpretation of the Constitutional Court judge is only a method of legal discovery/rechtsvinding against existing rules, but it is not easy to apply to procedural law. Third, the finding of conditional inconstitutionality in the Constitutional Court's decision Number: 46/PUU-VIII/2010 provides a new interpretation of Article 43 paragraph (1) of Law Number: 1 of 1974 concerning Marriage which is conditionally inconstitutional, namely inconstitutional as long as the verse is interpreted as eliminating civil relations with men who can be proven based on science and technology and/or other evidence according to law having blood relations as the father. Fourth, the juridical consequences after finding unconstitutional conditions provide legal guarantees and certainty for a child born out of wedlock, however, it is very difficult to obtain recognition from the biological father and/or to obtain evidence based on science and technology and/or other evidence. related to blood relations with biological fathers.